COGNITIVE LOSS AND FUNCTIONAL DEPENDENCE IN LONG-LIVED ELDERLY IN HOMES FOR THE AGED - Renato Novaes Chaves; Pollyanna Viana Lima; Tatiane Dias Casimiro Valença; Elaine dos Santos Santana; Maykon dos Santos Marinho; Luciana Araújo dos Reis (Universidade Federal do Paraná, 2017)
The objective was to assess the degree of functional dependence for the Basic Activities of Daily Living and the cognitive loss of long-lived elderly at two long-term care institutions for the elderly in the State of Bahia. Quantitative, cross-sectional research developed in 2016, involving 20 long-lived elderly. The interviewee's cognition was assessed by means of the Mini-Mental State Examination, the functional dependence for the Basic Activities of Daily Living by means of the Barthel Index and the Katz Scale, and the sociodemographic profile. The results appointed the prevalence of the age range between80 and 85 years (90.0%). The female sex presented a higher percentage of cognitive loss (28.5%), followed by illiterate men and women, (37.3%). The study supports the discussion based on the impact of the cognitive loss and the functional dependence for the health of the long-lived elderly.